Pemetaan Pola Kunjungan dan Cakupan Pelayanan Taman Vatulemo Pascarevitalisasi Berbasis GIS - Permata, Nike Dyah; Sari, Pawitra; Abdurrahman, Hadi; Khaerunnisa, Khaerunnisa (Universitas Pelita Bangsa, 2025)
One of the public places in the city of Palu is Vatulemo Park. In 2024, Vatulemo Park underwent a revitalization. The goal of this revitalization is to improve the quality and aesthetics of the park while expanding the coverage of public services in the surrounding area. The aim of this research is to use GIS to map the distribution of visitor patterns and the service coverage area of Vatulemo Park. The data collected through field observations, interviews, and visitor surveys were then analyzed using GIS. The study shows that visitors to Vatulemo Park do not only come from the park's service radius but also from outside the service radius. The visitation pattern is distributed based on location and the service coverage of the park, which can be optimized. The condition of the park can be clearly depicted through thematic maps that display the data. This study provides recommendations for park managers in planning the development of more efficient and inclusive infrastructure and services. Therefore, the analysis and visualization of the impact of revitalization on the visitation patterns and service coverage of Vatulemo Park can be successfully carried out using GIS techniques.